2004
DOI: 10.1162/089892904323057335
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing Components of Task Preparation with Functional Magnetic Resonance Imaging

Abstract: It is widely acknowledged that the prefrontal cortex plays a major role in cognitive control processes. One important experimental paradigm for investigating such higher order cognitive control is the task-switching paradigm. This paradigm investigates the ability to switch flexibly between different task situations. In this context, it has been found that participants are able to anticipatorily prepare an upcoming task. This ability has been assumed to reflect endogenous cognitive control. However, it is diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
225
1
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 280 publications
(275 citation statements)
references
References 46 publications
40
225
1
7
Order By: Relevance
“…Thus, the converging evidence suggests that the LPFC might not only be associated with task-order scheduling in dual-task performance but in any situation requiring the coordination of different interfering tasks (Duncan, 2001;Grafman, 1995). This idea is also consistent with assumptions of Brass and von Cramon (2004) who recently suggested that the IFJ (junction of IFS and precentral sulcus) constitutes an unique prefrontal cortical area, which is specifically associated with context-related updating of the general task representation. Such an updating process is likely to be part of the task-order scheduling mechanism, which is required particularly if the external context switches in different-order trials compared to same-order trials.…”
Section: Lateral Prefrontal Corticessupporting
confidence: 62%
See 2 more Smart Citations
“…Thus, the converging evidence suggests that the LPFC might not only be associated with task-order scheduling in dual-task performance but in any situation requiring the coordination of different interfering tasks (Duncan, 2001;Grafman, 1995). This idea is also consistent with assumptions of Brass and von Cramon (2004) who recently suggested that the IFJ (junction of IFS and precentral sulcus) constitutes an unique prefrontal cortical area, which is specifically associated with context-related updating of the general task representation. Such an updating process is likely to be part of the task-order scheduling mechanism, which is required particularly if the external context switches in different-order trials compared to same-order trials.…”
Section: Lateral Prefrontal Corticessupporting
confidence: 62%
“…Coull & Nobre, 1998;Herath, Klingberg, Young, Amunts, & Roland, 2001;Schubotz, Friederici, & von Cramon, 2000; see as well Schubert & Szameitat, 2003). Taken together, we think that task-order scheduling operates, at least partly, at the level of the tasks (see also Brass & von Cramon, 2004).…”
Section: Parietal Corticesmentioning
confidence: 77%
See 1 more Smart Citation
“…The role of the IFJ in WM and cognitive control: Uploading relevant rule information As we mentioned before, studies have shown the IFJ to be crucially involved in cognitive control and, more specifically, in task switching (Brass and von Cramon, 2002, 2004a, 2004bBrass et al, 2005;Derrfuss et al, 2005;Dove et al, 2000;Kim et al, 2012;Sylvester et al, 2003). Studies have also observed the IFJ to be involved in interference control and updating (e.g., Braver et al, 1997;de Fockert et al, 2004;Derrfuss et al, 2004Derrfuss et al, , 2005Mead et al, 2002;Roth et al, 2009;Sylvester et al, 2003).…”
Section: The Nature Of Wm Resources: Domain-general Time-based Resourmentioning
confidence: 91%
“…Task switching has been related to a fronto-parietal network (see Kim et al, 2012, for a meta-analysis). In the frontal cortex, one of the regions that have been most consistently observed in neuroimaging studies of task switching is the Inferior Frontal Junction (IFJ; Brass et al, 2005;Brass and von Cramon, 2002, 2004a, 2004bDerrfuss et al, 2005;Dove et al, 2000;Sylvester et al, 2003). The IFJ is situated at the junction of the precentral sulcus and the inferior frontal sulcus and, as such, anatomically perfectly suited for task switching and task management because it is located at the border of the premotor and prefrontal cortices (Brass and von Cramon, 2002).…”
Section: Introductionmentioning
confidence: 99%